Electrochemical Sensor Based on Molecularly Imprinted Polymer-Aptamer Hybrid Receptor for Voltammetric Detection of Thrombin. Issue 2 (4th January 2019) - Yang, Shaoming; Teng, Yu; Cao, Qiang; Bai, Chaopeng; Fang, Zhili; Xu, Wenyuan
Abstract : In this work molecularly imprinted polymer (MIP)-aptamer (Apt) hybrid recognition sensor based on nanocomposites of reduced graphene oxide (rGO) and gold nanoparticles (AuNPs) was reported. The glassy carbon electrode (GCE) was first modified with rGO and AuNPs. Then thrombin-Apt composites were obtained by the incubation of thiolated thrombin aptamer and template thrombin. Subsequently thrombin-aptamer composites were immobilized onto AuNPs/rGO/GCE through the Au-S bond between AuNPs and thiol group at the terminal of aptamer. Finally MIP-Apt hybrid recognition sensor was prepared by the electropolymerization of thionine. Using the polythionine as the probe, cyclic voltammetry, electrochemical impedance spectroscopy and differential pulse voltammetry were performed to characterize the MIP-Apt sensor. Adsorption kinetic model was established to obtain kinetic binding constants and equilibrium current. Due to hybrid recognition of MIP and Apt, MIP-Apt sensor has faster rebinding rate, better selectivity and sensitivity, comparing with non-molecularly imprinted sensor and non-aptamer molecularly imprinted sensor. The MIP-Apt sensor exhibited good linear response from 2.5 × 10 −9 mg/mL to 1.3 × 10 −6 mg/mL for thrombin with a detection limit of 1.6 × 10 −10 mg/mL.